Strategi Penyelesaian Pembiayaan Kredit Pemilikan Rumah (KPR) Bermasalah DI PT. Bank Sumut Syariah KCP Stabat - Sumiati, Sri Wahyuni, Khairani Sakdiah (CV. Pusdikra Mitra Jaya, 2023)
This study aims to find out, namely the implementation of mortgage financing (KPR), the factors that cause problematic housing credit (KPR) financing and strategies for solving problematic housing credit (KPR) financing at PT. Bank SUMUT Syariah KCP Stabat at PT. Bank SUMUT Syariah KCP Stabat. The research method used in this study is a descriptive qualitative research method with an empirical approach. The results of the study explain that the implementation of mortgage financing (KPR) at PT. Bank SUMUT Syariah KCP Stabat has several stages, namely completing files, financing assessment, financing decisions, contract agreements, and disbursement of funds. Factors that cause problematic financing in Home Ownership Credit Financing (KPR) products at PT. Bank SUMUT Syariah KCP Stabat consists of internal factors, namely factors originating from PT. Bank SUMUT Syariah KCP Stabat and external factors originating from the customer. Settlement of Problematic Financing in Home Ownership Credit (KPR) Financing Products at PT. Bank SUMUT Syariah KCP Stabat is carried out by means of: subrogation, sale of collateral for financing, repayment of financing by providing a reduction in arrears, settlement of civil disputes through basyarnas, collection of receivables through religious courts, auction of pre-auction financing collateral through private auction houses, legal remedies against personal guarantees ( borgtocht) and or corporate guarantee, and bankruptcy. The steps taken by PT. Bank SUMUT Syariah KCP Stabat in Troubled Housing Loans (KPR) Financing is to appoint employees to conduct customer development, conduct training on problem financing, work closely with the auction office.